Forecasting banking system liquidity using payment system data in Uzbekistan - Shakhzod Abdullaevich Makhmudov (Graduate Institute of International and Development Studies, 2025)
Forecasting banking system liquidity is crucial for the effective monetary policy implementation. This study investigates the effectiveness of various econometric and machine learning models in predicting the autonomous factors of banking system liquidity. The research compares widely used econometric models such as SARIMA, Exponential Smoothing, and Prophet alongside machine learning models like Random Forest, applying various preprocessing techniques, including power transformations, scaling, and trend-cycle decomposition. Moreover, ensemble methods, like weighted blending and stacking, were used to improve accuracy. Experimental results indicate that SARIMA was the best individual model, but ensemble with Prophet and Random Forest further improved forecast performance. Neural network models underperformed potentially due to challenges in optimizing their architectures. Future research intends to explore multivariate and structural models, as well as advanced neural architectures, to enhance predictive accuracy.
Keywords: E52; C22; C52; C53; E42; 330; Monetary Policy; Time-Series Models; Model Evaluation and Selection; Forecasting and Other Model Applications; Payment Systems